2018
DOI: 10.1038/s41467-017-02517-w
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the 1+7 configuration of ribonucleoprotein complexes for influenza A virus genome packaging

Abstract: The influenza A virus genome is composed of eight single-stranded negative-sense RNAs. Eight distinct viral RNA segments (vRNAs) are selectively packaged into progeny virions, with eight vRNAs in ribonucleoprotein complexes (RNPs) arranged in a specific “1+7” pattern, that is, one central RNP surrounded by seven RNPs. Here we report the genome packaging of an artificially generated seven-segment virus that lacks the hemagglutinin (HA) vRNA. Electron microscopy shows that, even in the presence of only seven vRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 46 publications
1
43
0
Order By: Relevance
“…In our previous report, 7-segmented (HA segment-deficient) IAV incorporated ribosomal RNAs into its virion (37). Thus, we examined the presence of 18S ribosomal RNA (rRNA) in purified recombinant virus, and found a greater amount of 18S rRNAs in OK-RG particles as compared to D/OK-clone particles (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous report, 7-segmented (HA segment-deficient) IAV incorporated ribosomal RNAs into its virion (37). Thus, we examined the presence of 18S ribosomal RNA (rRNA) in purified recombinant virus, and found a greater amount of 18S rRNAs in OK-RG particles as compared to D/OK-clone particles (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…IAV and IBV incorporate eight RNPs arranged in a specific pattern “1+7”, in which seven RNPs surround the central one (40, 43, 44). Surprisingly, artificially generated 7-segmented IAV, which lacks an HA segment, incorporated rRNA as the eighth RNP instead of an HA segment (37). Interestingly, ICV and IDV both possess a 7-segmented genome, yet also incorporated 8 RNPs, although inclusion of rRNA in virions was not assessed (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1 + 7 configuration may have a mechanistic function, as it is also conserved in type C and D viruses that only possess 7 vRNAs ( 36 ). Further supporting the mechanistic concept, it was recently shown that IAVs can package cellular ribosomal RNA (as a vRNP) when one of the vRNAs is made unavailable ( 37 ), possibly explaining how type C and D viruses acquire their “eighth” vRNA.…”
Section: Influenza Virusesmentioning
confidence: 89%
“…wrapped around a protein core which is composed of the trimeric polymerase complex PA/P3, PB1, PB2, and multiple copies of nucleoprotein (NP), forming a viral ribonucleoprotein complex (vRNP). It was suggested that seven vRNPs are coordinated around the remaining one forming a "7 plus 1" pattern within the virion (5). Recent results demonstrated that the genomes of ICV and IDV also adopt this pattern, although they only encompass seven gene segments (6).…”
mentioning
confidence: 99%